The Relationship Between Hormonal Contraceptive Use and Breast Cancer Incidence at Dr. Pirngadi Regional General Hospital, Medan - Filzah Aqilatul Hanisah; Hendrianto Hendrianto (CV. Inara, 2025)
Breast cancer remains a significant public health concern in Indonesia, with emerging evidence suggesting that hormonal contraceptive type influences not only cancer incidence but also tumor aggressiveness. This cross-sectional study examined the relationship between hormonal contraceptive formulations and histopathological grading of breast cancer at RSUD Dr. Pirngadi Hospital, Medan. The study included 100 women with confirmed invasive breast cancer who were selected using the Lemeshow formula for sample size calculation. A structured data extraction form collected information on contraceptive type, duration of use, and Nottingham grading classification. Fisher's Exact Test and chi-square test analyzed associations between contraceptive types and grading categories. Results demonstrated that oral pill users predominantly developed well-differentiated cancers (51.7%), while injectable users predominantly developed poorly-differentiated tumors (56.3%), representing a highly significant inverse relationship (p-value = 0.000, OR = 0.105). Moderately-differentiated grading showed no significant association with contraceptive type. These findings indicate that contraceptive formulation substantially influences tumor characteristics beyond cancer occurrence alone. The study's cross-sectional design limits causal inference, and future prospective cohort studies with larger samples and comprehensive molecular characterization are needed. The pronounced predominance of aggressive tumor phenotypes among injectable contraceptive users necessitates more intensive breast cancer screening protocols and improved patient counseling regarding differential cancer risks across contraceptive formulations in Indonesian populations.